Analisis Profitabilitas Terhadap Pembiayaan Mudharabah dan Musyarakah sebagai Upaya Alternatif dalam Peningkatan Profit pada Perbankan Syariah di Tengah Tantangan Ekonomi Global - Dhamar Djati Sasongko; Fadhilatul Amaliya; Isna Nurul Hasanah; Fani Rahmasari; Fidanzani Zulfadikhan Azhar; Dewi Sekar Pembayun; Adhirajasa Shidqi Muhammad; Nur Rofiq (BADAN PENERBIT STIEPARI PRESS, 2025)
Islamic banking faces significant challenges in maintaining profitability amid global economic instability. One potential strategy is optimizing profit-sharing financing schemes, such as mudharabah and musyarakah. This study aims to explore the relationship between profitability and the implementation of these financing schemes while assessing their effectiveness in enhancing the profitability of Islamic banks. A quantitative approach with descriptive-literature analysis is used to examine the correlation between profitability and profit-sharing financing. The data is obtained from Islamic banking financial reports over the past five years. The findings indicate that mudharabah and musyarakah positively contribute to Islamic banking profitability. Mudharabah is more effective in business sectors with measurable risks, whereas musyarakah offers greater flexibility for long-term investments. However, the implementation of these schemes faces challenges such as high risks and market uncertainty. Therefore, stronger risk mitigation strategies and supportive regulations are necessary to ensure that profit-sharing financing can have an optimal impact on the profitability growth of Islamic banking.